# Infix expressions

### From HaskellWiki

Revision as of 03:01, 21 March 2006 by BrettGiles (Talk | contribs)

## 1 Disclaimer

This is a **WORK IN PROGRESS**, transcribed from an email log on haskell-prime@haskell.org.

## 2 Mail info

The original header posted here:

From: dons@cse.unsw.edu.au (Donald Bruce Stewart) To: Simon Peyton-Jones <simonpj@microsoft.com> Date: Wed, 15 Mar 2006 23:25:34 +1100 Cc: haskell-prime@haskell.org, oleg@pobox.com Subject: Re: Infix expressions

This refered to a variety of articles, the original was said to be: haskell-cafe message

## 3 The solution

In Haskell we write`f`

xs `zipWith (+)` ys

Chung-chieh Shan and Dylan Thurston showed the Haskell98 solution for exactly the same example, in their article `Infix expressions', back in 2002 in the article referenced above.

For ease of reference, here's their elegant solution:

infixr 0 -:, :- data Infix f y = f :- y x -:f:- y = x `f` y main = print $ [1,2,3] -: zipWith (+) :- [4,5,6]

For completeness, here's the `dual':

infixr 5 -! (-!) = flip ($) infixr 5 !- (!-) = ($) add2 x y = x + y add3 x y z = x + y + z add4 x y z u = x + y + z + u testa1 = 1 -! add2 !- 3 + 4 testa2 = 1 -! add3 1 !- 3 + 4 testa3 = 1 - 2 -! add4 1 5 !- 3 * 4